In vivo bioluminescence imaging of vascular remodeling after stroke - Adamczak, Joanna M.; Schneider, Gabriele; Nelles, Melanie; Que, Ivo; Suidgeest, Ernst; van der Weerd, Louise; Löwik, Clemens; Hoehn, Mathias (Frontiers in Cellular Neuroscience, 2014)
Thrombolysis remains the only beneficial therapy for ischemic stroke, but is restricted to a short therapeutic window following the infarct. Currently research is focusing on spontaneous regenerative processes during the sub-acute and chronic phase. Angiogenesis, the formation of new blood vessels from pre-existing ones, was observed in stroke patients, correlates with longer survival and positively affects the formation of new neurons. Angiogenesis takes place in the border zones of the infarct, but further insight into the temporal profile is needed to fully apprehend its therapeutic potential and its relevance for neurogenesis and functional recovery. Angiogenesis is a multistep process, involving extracellular matrix degradation, endothelial cell proliferation, and, finally, new vessel formation. Interaction between vascular endothelial growth factor and its receptor 2 (VEGFR2) plays a central role in these angiogenic signaling cascades. In the present study we investigated non-invasively the dynamics of VEGFR2 expression following cerebral ischemia in a mouse model of middle cerebral artery occlusion. We used a transgenic mouse expressing firefly luciferase under the control of the VEGFR2 promotor to non-invasively elucidate the temporal profile of VEGFR2 expression after stroke as a biomarker for VEGF/VEGFR2 signaling. We measured each animal repetitively up to 2 weeks after stroke and found increased VEGFR2 expression starting 3 days after the insult with peak values at 7 days. These were paralleled by increased VEGFR2 protein levels and increased vascular volume in peri-infarct areas at 14 days after the infarct, indicating that signaling via VEGFR2 leads to successful vascular remodeling. This study describes VEGFR2-related signaling is active at least up to 2 weeks after the infarct and results in increased vascular volume. Further, this study presents a novel strategy for the non-invasive evaluation of angiogenesis-based therapies.